PEMODELAN DIAGRAM UML SISTEM PEMBAYARAN TUNAI PADA TRANSAKSI E-COMMERCE - Muhamad Syarif; Wahyu Nugraha (STMIK KAPUTAMA, 2020)
The use of technology in the business world can help make work easier. Technology makes data stored more standardized and processing data into information faster. Sales transactions and payment transactions are business activities that need attention, both of these transactions need to be monitored so that business processes can run well and as desired. This research designs sales and payment information systems, payment transactions can be made in cash on e-commerce sales systems. The system is designed using UML diagram modeling to illustrate the needs and what content can be done by the system. Payment system modeling is expected to be a tool that can help transaction processing become more standardized and produce reports quickly. Keywords: Modeling UML, Payment, Cash, E-Commerce